Analysis of Fulfillment of Four Aspects in Drinking Water and Incidence of Stunting in Coastal Areas: Case Study of Paluh Sibaji Village, Pantai Labu Sub-district - Sri Malem Indirawati; Umi Salmah; Taufik Ashar; Arifa Masyitah Panjaitan; Risanti Febrine Ropita Situmorang; Annisa Rizka Lestari (Universitas Islam Negeri Sumatera Utara, Medan, 2024)
Paluh Sibaji Village, Pantai Labu District, in a coastal area located in Deli Serdang district,has only 0.5% reduction in stunting from 2022 to 2023. The prevalence of stunting in Deli Serdang District was 13.9 in 2023 has increased by 1.4 percent from 2021. Pantai Labu sub-district is located in a coastal area with 60 cases of stunting, 10 of which were found in Paluh Sibaji village. Proper sanitation is an indirect factor causing stunting, including meeting the four aspects (quality, quantity, continuity and affordability) in drinking water. This research aimed to analyze the Four aspect of drinking water sources with stunting incidents. This type of research was analytical with a cross sectional study design. The population was 375 houses of mothers with toddlers and 141 houses sample spread across 4 hamlets. The sampling technique used was cluster sampling and data analysis used Chi square statistical test by using SPSS version 25. Data were collected using a questionnaire designed in the ceting card tool which was applied via Android. The results of the research found that 16.3% of children under five were stunted and based on the type of clean water source, namely dug wells 22 people (15.6%), drilled wells 33 people (23.4%), and municipal waterworks 86 people (61.0%), only 3.5% of houses met the four aspects. The statistical test results showed that the variables of fulfilment of the four aspects of drinking water, and drinking water treatment were not related with the incidence of stunting (Pv>0.05). Other basic sanitation factors besides clean water and drinking water sources can become environmental management priorities in an effort to provide proper sanitation in Paluh Sibaji village to reduce stunting. Keyword: Affordability, Continuity, Stunting, Quality, Quantity of Drinking Water